Effect of PLGA Concentration in Electrospinning Solution on Biocompatibility, Morphology and Mechanical Properties of Nonwoven Scaffolds; Technologies; Vol. 11, iss. 5 - Badaraev A. D. Arsalan Dorzhievich; Tran Tuan Hoang; Drozd A. G. Anastasiya Gennadjevna; Plotnikov E. V. Evgeny Vladimirovich; Dubinenko G. E. Gleb Evgenjevich; Kozelskaya A. I. Anna Ivanovna; Rutkowski S. Sven; Tverdokhlebov S. I. Sergei Ivanovich (2023, 2023)
Title screen